The Pattern of Nahdlatul Ulama’s Ijtihad - Mustopa Kamal; Ayi Ishak Sholih Muchtar (Istinbath | Jurnal Penelitian Hukum Islam, 2020)
In line with the socio-religious dynamics in society, various problems surrounding fiqh have also developed, most of which have not been absorbed in the legal thinking of the scholars. Concerning issues commonly referred to as masa’il fiqhiyyah al-hadithah, scholars have institutional mechanisms to solve these problems. Nahdlatul Ulama, the most prominent Islamic religious organization in the country, is also concerned with masa’il fiqhiyyah al-hadithah through the Bahtsul Masa’il (BM-NU) mechanism. However, the BM-NU legal istinbath framework is unique, because it is different from the legal istinbath framework that previous scholars had—such as the legal istinbath framework used by Abu Hanifah and Muhammad Ibn Idris al-Syafi’i, also different from the legal istinbath framework with mass organizations. Other Indonesian Islam—such as the legal istinbath framework of the Persis Hisbah Council and the legal istinbath framework of Majlis Tarjih and the Development of Muhammadiyah Islamic Thought. The uniqueness is mainly because the legal istinbath framework adopted by BM-NU tends to present themselves as muttabi’ ulama and does not present themselves as mujtahid clerics as is generally understood by fuqahâ.